Synthesis of bio-based monomer from vegetable oil fatty acids and design of functionalized greener polyester - Abd. Rahim, Noor Farisha; Watanabe, Kohtaro; Ariffin, Hidayah; Andou, Yoshito; Hassan, Mohd Ali; Shirai, Yoshihito (Chemical Society of Japan, 2014)
In order to design sustainable materials from vegetable oil-based fatty acids, we propose herewith a method to obtain unsaturated dicarboxylic acids as a polymerizable monomer through metathesis reaction of oleic and linoleic acids with the 2nd generation Grubbs catalyst. Subsequently, functional green polyester was produced from dicarboxylic acids and aromatic diol. Dicarboxylic acid having similar structure i.e., octadec-9-enedioic acid was successfully obtained from metathesis of both oleic and linoleic acids. Condensation polymerization of octadec-9-enedioic acid with 1,6-hexanediol and 4,4′-biphenol was carried out and it was shown that polymer with aromatic backbone had higher glass-transition temperature than aliphatic polyester.